Research Progress on Heat Transfer of Liquid-liquid Two-phase Slug Flow in Microchannels - 庄晓如; 李翔; 杨智 (Zhileng xuebao)
With the rapid development of micro-electro-mechanical system (MEMS) technology, heat dissipation with high heat flux in limited space has become a key problem restricting the efficient and stable operation of the equipment. Heat dissipation technology of liquid-liquid two-phase flow in microchannels has emerged as an effective solution to this problem. In this paper, the classification of liquid-liquid two-phase flow patterns in microchannels was first reviewed. Compared with other flow patterns, slug flow is a critical flow pattern in it, which has significantly enhanced heat and mass transfer performance. Then, this paper summarizes and analyzes the current research progress on heat transfer of liquid-liquid two-phase slug flow in microchannels. At present, most studies in this field rely heavily on numerical simulations, with relatively few experimental investigations. Existing numerical models often simplify the complexities of physical phenomena, and many have not been validated against experimental data. Furthermore, these models frequently employ macroscopic numerical methods, such as Volume of Fluid (VOF) and Finite Volume Method (FVM), to capture the two-phase interface. However, the accuracy of these models in calculating the flow field, temperature field, and the rates of heat and mass transfer in two-phase interface still requires further verification. Experimental studies tend to focus on mini-channels, primarily measuring macro-scale global data, such as total pressure drop, overall heat transfer coefficient, and average fluid temperature. There is a notable lack of research involving micro-scale local and instantaneous data, such as local heat transfer coefficient and detailed flow and temperature fields. Finally, the future research direction of heat transfer for liquid-liquid two-phase slug flow in microchannels is prospected.